If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -1x = 20 + 5x Solving 2 + -1x = 20 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 2 + -1x + -5x = 20 + 5x + -5x Combine like terms: -1x + -5x = -6x 2 + -6x = 20 + 5x + -5x Combine like terms: 5x + -5x = 0 2 + -6x = 20 + 0 2 + -6x = 20 Add '-2' to each side of the equation. 2 + -2 + -6x = 20 + -2 Combine like terms: 2 + -2 = 0 0 + -6x = 20 + -2 -6x = 20 + -2 Combine like terms: 20 + -2 = 18 -6x = 18 Divide each side by '-6'. x = -3 Simplifying x = -3
| -x+7(x+8)=6x-(3x+1) | | 4n-3(n-2)=6n-5 | | 2x^2+8x+32= | | -18=9u | | 3x-5x+9=-21 | | 4y+22=2(2v-3) | | 4x+2x+12=18 | | 7x+6=7x-6 | | -12y=-24 | | -9+8+6d+7d= | | 0=y-2x | | 6x-16=8x-34 | | (11b-11)/5=(3b-2)/2 | | 5x-11+6=-20 | | 65=5v | | 6x-18=8x-34 | | 9x+5=-94 | | 10/7+1/2t=7 | | 2y+-3=-2y+13 | | 6p^2+10p-36= | | 3(x-0.2)+.1x=5.6 | | x^2+4x+y^2-8y+10=0 | | 4b-8=2b+16 | | (4x-1)+(3x+1)+(x+4)=12 | | 8s-1=3(6-2s) | | -2y+10=-2(2y+1) | | 4(x-6)-6=-30 | | 6u+39=-7u | | 6+n/9=8 | | 4n+7=2n+8 | | x+(32+x)=46 | | 1/4*-20 |